Implementasi Kuota 30% Calon Legislatif Perempuan di Gresik pada Pemilu Tahun 2014 - Hidayati, Alif (Prodi Siyasah Jinayah (Hukum Tata Negara dan Hukum Pidana Islam) Fakultas Syariah dan Hukum UIN Sunan Ampel Surabaya, 2014)
Abstract: This paper addresses the issue of how the implementation of the 30% quota of the women legislative candidates in the electoral district 4 in Gresik in 2014 general election according to Undang-Undang No. 8 tahun 2012 and the political (siyasah) jurisprudence. The data are collected through interview and a study of the texts related to the problem. They are then analyzed using the political (siyasah) jurisprudence approach and accomplished by inductive framework. The study concludes that the implementation of the 30% quota of the women legislative candidates in the electoral district 4 in Gresik has been in conformity with UU No. 8 tahun 2012 and Peraturan KPU No 7 tahun 2013. It is recorded that the women legislative candidates, in the list of the fixed candidates, are 34.61% or 36 people of the 104 candidates in the electoral district 4. However, the final result shows that the 34.61% of the women legislative candidates have not met the 30% quota. In fact, there are only 2 people (20%) of the 10 council members who represent the electoral district 4 in Gresik. In Islam, there is none of the discussion of the application of the 30% quota of the women legislative representation in parliament. Within the perspective of the political (siyasah) jurisprudence, the 30% quota of the womenâs representation in parliament are not contrary to the principles of Islam as long as they have the capacity and capability as a leader. It is because Islam adheres the principle of equal right between men and women as mentioned in chapter al-Taubah, verse 71.Keywords: The 30% quota, womenâs representation, general election, legislative